The Gambia : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper; Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2006)
This Joint Staff Advisory Note reviews the first Annual Progress Report (APR) of The Gambia's Poverty Reduction Strategy Paper (PRSP). The APR indicates that The Gambia's progress in implementing the PRSP has been uneven. Slow implementation mainly reflected low capacity, a lack of commitment, and poor prioritization of policies implemented in 2002-03. Among the five basic components, the authorities made the most progress in increasing access to basic social services. By contrast, they did not achieve most macroeconomic targets for 2002 and 2003.